PENERAPAN MEDIA QUIZIZZ TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SDN TUNJUNG 1 - Afrida, Desvia Nur; Emelya Qoffayana; Nuril Mumtaz; Annisa Aditya ramadhani; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the application of Quizizz digital-based learning media on student learning outcomes in Natural and Social Sciences (IPAS) subjects in class IV SDN Tunjung 1. The background of this study is the low student learning outcomes and the lack of interest and active participation in the conventional learning process. This study used a quantitative approach with a one-group pretest-posttest pre-experiment design. The research subjects totaled 16 students. Data collection techniques were carried out through pretest and posttest which were analyzed using descriptive and inferential statistics through t-test. The results showed that there was an increase in the average score from 63.63 in the pretest to 80.75 in the posttest. The calculated t value of 17.1185 > t table 2.131 indicates a significant difference before and after treatment. These findings indicate that the use of Quizizz media has a positive impact on improving student learning outcomes. Therefore, Quizizz can be an alternative learning media that is effective, interactive, and in accordance with technological developments.